Disorder, not just state of risk: Meta-analysis of functioning and quality of life in people at high risk of psychosis. (September 2015) - Fusar-Poli, Paolo; Rocchetti, Matteo; Sardella, Alberto; Avila, Alessia; Brandizzi, Martina; Caverzasi, Edgardo; Politi, Pierluigi; Ruhrmann, Stephan; McGuire, Philip
Abstract : Background: The nosology of the psychosis high-risk state is controversial. Traditionally conceived as an 'at risk' state for the development of psychotic disorders, it is also conceptualised as a clinical syndrome associated with functional impairment. Aims: To investigate meta-analytically the functional status of patients at high clinical risk for psychosis and its association with longitudinal outcomes. Method: Three meta-analyses compared level of functioning ( n = 3012) and quality of life (QoL) ( n = 945) between a high-risk group, a healthy control group and group with psychosis, and baseline functioning in people in the high-risk group who did or did not have a transition to psychosis at follow-up ( n = 654). Results: People at high risk had a large impairment in functioning ( P <0.001) and worse QoL ( P = 0.001) than the healthy control group, but only small to moderately better functioning ( P = 0.012) and similar QoL ( P = 0.958) compared with the psychosis group. Among the high-risk group, those who did not develop psychosis reported better functioning ( P = 0.001) than those who did. Conclusions: Our results indicate that the high-risk state is characterised by consistent and large impairments of functioning and reduction in QoL similar to those in other coded psychiatric disorders.